Alterações morfológicas dos ovários de Rhipicephalus microplus submetidos ao tratamento com Lippia sidoides e Lippia gracilis - Penha, Tatiane Aranha da (2016)
The tick Rhipicephalus microplus, found in tropical and subtropical regions, has caused great harm to the Brazilian livestock. The damage caused by this tick the Brazilian livestock exceeds three billion dollars. Verbenaceae Lippia genus, especially the species L. sidoides and L. gracilis, have been reported with potential activity in larvae and R. microplus females. Therefore, the aim of this study was to evaluate the acaricide activity of L. sidoides and L. gracilis essential oils and its major compounds thymol and carvacrol and characterize morphological changes in ovaries of R. microplus females from lethal concentrations 50 (LC50) and 75% (LC75) of the study population. After selection of the genotypes (LGRA-106, LGRA-201, LSDI-102 and LSDI-103), groups of 10 engorged females were subjected to the immersion test in essential oils at different concentrations and DMSO 3% was used for the control. After seven days, the ticks were dissected in phosphate buffer solution and the ovaries were fixed in 2.5% glutaraldehyde for a period of 24 hours. The tissues were dehydrated and embedded in plastic molds Leica resin for histological analysis. The results visualization and characterization of the ovary and the different stages of development of oocytes. In the control group, treated with 3% DMSO, changes in the tissues have not been verified. In groups treated with the L. gracillis oils and L. sidoides oils, vacuolization was observed in oocytes II, III, IV and V, cell membrane disintegration in oocytes II, III, IV and V, with complete morphological deformation of oocytes IV and V. The major compounds, thymol and carvacrol seem to be actively working on these changes. The results showed activity of the different genotypes of the essential oils and their major compounds in larvae and females of R. microplus and allowed to elucidate the mechanism of action of the same in the oogenesis of the females, leading to believe that the compounds tested are promising for the development of acaricide products.